Uncertainty and Climate Variability in the Design and Operation of Water Resources Projects : Examples and Case Studies, Volume 2. Annexes - Rodriguez-Iturbe, Ignacio; Valdes, Juan B. (Washington, DC: World Bank, 2013)
There are two common problems in flood hydrology: 1) estimate the return period for a given flood; and 2) estimate the flood for a given return period. A commonly used procedure to solve these problems is to fit a probability density function such as the Gumbel, Pearson type three or the generalized extreme value distributions to the historical data. The Pearson probability distribution was named after the statistician Pearson, it is also called the three-parameter gamma distribution. The Mann-Kendall test is a non-parametric test for identifying trends in time series data. The test compares the relative magnitudes of sample data rather than the data values them. One benefit of this test is that the data need not conform to any particular distribution. The data values are evaluated as an ordered time series. Each data value is compared to all subsequent data values. There are basically two approaches to downscale coupled climate model projections: statistical and dynamic downscaling.